PENYAKIT KULIT SEBAGAI PEMBANGUN STRUKTUR NARATIF: TINJAUAN NARATOLOGIS HIKAYAT AGUNG SAKTI KARYA MUHAMMAD BAKIR - Dewojati, Cahyaningrum; Winarti, Daru; Udu, Sumiman; Windayanto, Riqko Nur Ardi (UI Scholars Hub, 2024)
This research aims to discover the role of skin diseases in the narrative structure of M. Bakir’s Hikayat Agung Sakti as well as its surrounding ideological, social, political, and cultural contexts. Mieke Bal’s narratological theory was applied to map and analyze the elements of the fabula: event, time, actor, and location. Methodologically, this research consisted of two levels: text and context. At the first level, lingual data were collected using the note-taking technique and then explained interpretatively using relevant theoretical concepts. At the second level, data were collected through literature study on ideology and context. The text and context data were explained through dialectics and interreference. This research yielded several main results. First, skin diseases (itches, smallpox, scabs, and Tinea corporis) are attached to the elements of the fabula. These diseases change circumstances, shape events and time, infect the characters (the Gods), and change the locations (from heaven to earth). Skin diseases were found to be the building block of the narrative structure. In this role, skin diseases become a means of articulating Islamism. This narrative is linked to the development of Islam in Malay-speaking lands and political resistance to polytheistic Hinduism, which is placed in opposition to the monotheistic Islam which places Allah as the only deity. This ideology was articulated and written down as a literary work to be disseminated among local Straits-born Chinese. This is also contextually related to the issues of manuscript rental, diseases in Malay tradition, and spread of diseases in Batavia in the 19th century.